2021
DOI: 10.1302/2633-1462.210.bjo-2021-0059.r1
|View full text |Cite
|
Sign up to set email alerts
|

Theatre efficiency in COVID-19 pandemic conditions: The collaborative experience of four level 1 major trauma centres in the UK

Abstract: Aims As the world continues to fight successive waves of COVID-19 variants, we have seen worldwide infections surpass 100 million. London, UK, has been severely affected throughout the pandemic, and the resulting impact on the NHS has been profound. The aim of this study is to evaluate the impact of COVID-19 on theatre productivity across London’s four major trauma centres (MTCs), and to assess how the changes to normal protocols and working patterns impacted trauma theatre efficiency. Methods This was a colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This has major implications for the way surgical services and operating theatres are managed, and the information needed to support that management. With hospitals already under pressure, most have faced additional strain arising from COVID‐19 hospitalisations with reports of delays to all aspects of theatre use, and consequently decreases in theatre efficiency 2–5 . Efficient theatre management is particularly important as many countries enter a ‘COVID‐19 normality’ moving from pandemic status to endemic.…”
Section: Introductionmentioning
confidence: 99%
“…This has major implications for the way surgical services and operating theatres are managed, and the information needed to support that management. With hospitals already under pressure, most have faced additional strain arising from COVID‐19 hospitalisations with reports of delays to all aspects of theatre use, and consequently decreases in theatre efficiency 2–5 . Efficient theatre management is particularly important as many countries enter a ‘COVID‐19 normality’ moving from pandemic status to endemic.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of SARS-CoV-2 infection on operating room efficiency in London’s four busiest trauma centers was studied by Jeyaseelan et al They found that although the frequency of open reduction and internal fixation surgeries decreased in 2020, the number of orthopedic patients increased. The median time between sending a patient and their arrival in the anesthetic chamber increased significantly [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ [21][22][23]25,26,[66][67][68] Head and Neck Facial trauma surgeries prioritized by urgency balancing transmission risks with time minimization key -under 5 minutes from incision to cuff inflation. Home drain removal successfully implemented for most neck surgeries, preventing hazardous in-person encounters while telemedicine managed rhinology cases effectively.…”
Section: Oncologicmentioning
confidence: 99%